Open Source Software: Quality Verification 9th IFIP WG 2.13 International Conference, OSS 2013, Koper-Capodistria, Slovenia, June 25-28, 2013. Proceedings - Petrinja, Etiel; Succi, Giancarlo; Ioini, Nabil; Sillitti, Alberto; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 9th International IFIP WG 2.13 Conference on Open Source Systems, OSS 2013, held in Koper-Capodistria, Slovenia, in June 2013. The 18 revised full papers and 3 short papers presented were carefully reviewed and selected. The papers are organized in topical sections on innovation and sustainability; practices and methods; FOSS technologies; security and open standards; and business models and licensing.
Innovation and sustainability -- Practices and methods -- FOSS technologies -- Security and open standards -- Business models and licensing.
Keywords: Computer science; Software engineering; Education; Computers -- Law and legislation; Information Systems; Computer Science; Legal Aspects of Computing; Software Engineering; Management of Computing and Information Systems; Computers and Society; Computers and Education